Translating purpose and mindset into positive impact through shared vision, compassion, and energy—a comparative study of seven organizations - Leah, Joseph S. (Frontiers in Psychology, 2024)
How does the quality of relationships in an organization affect the ability to deliver positive impact? How do organizations that explicitly state the intention to be "positive impact companies" differ from traditional entrepreneurial companies? This study explores the conditions under which business leaders turn their organizations toward generating prosperity for all stakeholders, achieving positive societal outcomes, improving human wellbeing, and delivering great business results.Seven case study companies are examined based on interviews with three executives from each firm, including the CEO. All seven companies are privately owned small/medium sized businesses from a cross section of industries and diverse geographic bases, ranging from Michigan to the Pacific Northwest, to Singapore, Egypt, and Florida. Four of the companies are considered "positive impact companies" (PICs) based on their organizational affiliations, while the other three are considered traditional entrepreneurial companies (TECs).The overall findings suggest that the core of positive impact leadership resides in a shift in the mindset of leaders toward one of connectedness and purpose, and that these factors influence the quality of relationships in organizations in a positive way whether the company is considered a PIC or a TEC. The results also suggest a close relationship between several core indicators of a fundamental shift in understanding about the role of business in society: shared values of human wellbeing, a common shared vision, an emphasis on collaboration and caring in organizations, and a long-term perspective toward the creation of shared economic prosperity.